Chemoselective formation and reaction of densely functionalised bicyclic tetramic acids and their biological activity - Moloney, M; Josa-Culleré, L; Thompson, A; Towers, C (Wiley, 2017)
Weinreb amide derivatives of tetramates may be effectively accessed by chemoselective Dieckmann reaction, and further react with Grignards in a fully chemoselective reaction, giving rise to unsaturated acyl derivatives not easily available by other routes. These systems are strong chelators of calcium, and some show potent activity against Gram positive bacteria, and one is a first-in-class proteasome inhibitor.